2023
DOI: 10.1007/s11423-023-10229-w
|View full text |Cite
|
Sign up to set email alerts
|

Do teaching staff trust stakeholders and tools in learning analytics? A mixed methods study

Abstract: Learning analytics (LA) has gained increasing attention for its potential to improve different educational aspects (e.g., students’ performance and teaching practice). The existing literature identified some factors that are associated with the adoption of LA in higher education, such as stakeholder engagement and transparency in data use. The broad literature on information systems also emphasizes the importance of trust as a critical predictor of technology adoption. However, the extent to which trust plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A separate study [47] explored trust's influence on the integration of LA within higher education. The results showed that educators displayed substantial trust in the competence of HEIs and the effectiveness of LA.…”
Section: Research Gapmentioning
confidence: 99%
“…A separate study [47] explored trust's influence on the integration of LA within higher education. The results showed that educators displayed substantial trust in the competence of HEIs and the effectiveness of LA.…”
Section: Research Gapmentioning
confidence: 99%